Aplikasi Penentuan Jenis Ikan Koi Berdasarkan Pembacaan Komposisi Warna Berbasis Android - Yasir Hasan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Purchasing koi fish can be done online and buyers will be satisfied because they can find out information on koi fish while surfing for information on koi fish that are sold online, but it is different from buying koi fish directly from the seller. Limited knowledge about the types of koi fish can make buyers confused and buy wrong. Buyers may ask directly to the seller, but the seller will not necessarily be fully served. The existence of an android application that can identify types of koi fish can help direct buyers and equip buyers to interact with sellers in koi fish transactions. Koi fish identification by android application is carried out by two determining factors. The first determining factor reads the color value by comparing the color value of the camera captured image with the values ??available in the database. The second determining factor is based on the texture motif found on the koi fish's body. The second determining factor is done if the first determining factor does not support determining the type of koi fish, such as the color composition is very complex to be compared.